PENDIDIKAN DALAM AL-QUR’AN KAJIAN PADA QS. AL-RAHMAN 1-4 - Abu Bakar, Abdul Syukur (Universitas Islam Negeri Alauddin Makassar, 2018)
Education is a planned and practical activity process that has goals to be achieved. Thus the importance of a goal, so it is not surprising that there are many studies among experts regarding the importance of education. Many books that study education, many theories have emerged, many patented good formulas from God come from humans regarding education. In the Qur'an there has never been found an educational concept which was stopped at a certain level, but education lasted a lifetime at all stages of human growth and development. This research is based on a research library in the QS study. Al Rahman 1-4 and various expert views on education. The combination of the understanding of the Qur'an with the theory of education experts will give birth to a generation that is intelligent in its mind, polite and prudently spiritual.